Investigation of ferromagnetic resonance and damping properties of CoFeB - (:unkn) unknown (ELSEVIER SCIENCE BV, 2019)
In this study, the influences of thin film thickness and post-annealing process on the magnetic properties of CoFeB thin films were investigated. The angular dependency and linewidth of the ferromagnetic resonance signal were used to explore the magnetic behavior of sputtered single-layer and trilayer thin film stacks of CoFeB. A micromagnetic simulation model was employed based on the metropolis algorithm comprising the demagnetizing field and in-plane induced uniaxial anisotropy terms with all relevant contributions. Our results reveal that the direction of magnetization changes from in-plane to out-of-plane as a result of the annealing process and induces a perpendicular magnetic anisotropy in the 1-nm thick CoFeB thin film. The ferromagnetic resonance (FMR) linewidth can be defined well by the intrinsic Gilbert damping effect and the magnetic inhomogeneity contribution in both as-grown and annealed samples. The difference between the linewidths of the single and trilayer film is mainly caused by the spin pumping effect on damping which is associated with the interface layers.
Keywords: Magnetic thin films; Ferromagnetic resonance; Ferromagnetic resonance linewidth; Magnetic anisotropy; CoFeB; PERPENDICULAR-ANISOTROPY; MAGNETIC-ANISOTROPY; TAB2 POWDERS